The Rivals : and Other Stories - Rozenfeld, Yonah, 1880-1944 (Judaic traditions in literature, music, and art., 2020)
""The Rivals and Other Stories" is a selection of eighteen early to mid-twentieth-century short stories by Russian immigrant author Jonah Rosenfeld, translated from their original Yiddish by Rachel Mines"--